2015
DOI: 10.1590/01000683rbcs20140391
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Matéria Seca E Acúmulo De Macronutrientes Na Parte Aérea Das Plantas De Niger

Abstract: RESUMOO estudo da marcha de absorção de nutrientes e da produção de matéria seca em razão do estádio de desenvolvimento das culturas é de fundamental importância para subsidiar estratégias de adubação. Este trabalho objetivou determinar a produção de matéria seca e o acúmulo de macronutrientes na parte aérea das plantas de Guizotia abyssinica (niger), em diferentes estádios de crescimento e desenvolvimento. O delineamento experimental foi em blocos ao acaso, com cinco repetições. Amostras da parte aérea das pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Low export of Ca by safflower (about 10%) was also verified for peanuts, sunflower, and niger crops by Feitosa et al (1993), Zobiole et al (2010), and Mauad et al (2015), respectively. According to Marschner (1995) and Maathuis (2009), Ca presents low mobility in the phloem, thus limited redistribution in the plant, and consequently reduced translocation to fruits and storage organs.…”
Section: Amounts Of Exported Macronutrientsmentioning
confidence: 57%
See 1 more Smart Citation
“…Low export of Ca by safflower (about 10%) was also verified for peanuts, sunflower, and niger crops by Feitosa et al (1993), Zobiole et al (2010), and Mauad et al (2015), respectively. According to Marschner (1995) and Maathuis (2009), Ca presents low mobility in the phloem, thus limited redistribution in the plant, and consequently reduced translocation to fruits and storage organs.…”
Section: Amounts Of Exported Macronutrientsmentioning
confidence: 57%
“…Zobiole et al (2010) also observed high N and P mobilization in sunflower achenes. Crusciol et al (2012) also found the same behaviour in castor bean, and Mauad et al (2015), in niger (Guizotia abyssinica)-an oilseed crop of the Asteraceae family. According to Castro et al (1999), in oleaginous plants N determines the equilibrium of accumulated protein content and oil production because of its influence on the metabolism and the synthesis of reserve compounds in the seeds.…”
Section: Amounts Of Exported Macronutrientsmentioning
confidence: 65%
“…O niger é uma planta dicotiledônea, herbácea anual (MAUAD et al, 2015), rico em ácidos graxos poli-insaturados, principalmente o ácido linoléico, cerca de 70% (RAMADAN & MÖRSEL, 2003). A cultura pode ser cultivada com sucesso em rotação de culturas (GETINET & SHARMA, 1996), melhorando as qualidades físicas, químicas e biológicas do solo e interrompendo ciclos de patógenos, agentes causadores de doenças.…”
Section: Introductionunclassified